PREVALENCE, MECHANISMS, AND MANAGEMENT OF CANCER-RELATED COGNITIVE IMPAIRMENT - Janelsins, Michelle C. (2014)
This review summarizes the current literature on cancer-related cognitive impairment (CRCI) with a focus on prevalence, mechanisms, and possible interventions for CRCI in those who receive adjuvant chemotherapy for non-central nervous system tumors and is primarily focused on breast cancer. CRCI is characterized as deficits in areas of cognition including memory, attention, concentration, and executive function. Development of CRCI can impair quality of life and impact treatment decisions. CRCI is highly prevalent; these problems can be detected in up to 30% of patients prior to chemotherapy; up to 75% of patients report some form of CRCI during treatment, and CRCI is still present in up to 35% of patients many years following completion of treatment. While the trajectory of CRCI is becoming better understood, the mechanisms underlying the development of CRCI are still obscure; however, host characteristics, immune dysfunction, neural toxicity, and genetics may play key roles in the development and trajectory of CRCI. Intervention research is limited, though strategies to maintain function are being studied with promising preliminary findings. This review highlights key research being conducted in these areas, both in patient populations and in animals, which will ultimately result in better understanding and effective treatments for CRCI.